Manors and markets economy and society in the Low Countries, 500-1600 - Bavel, B. J. P. van, 1964- (Oxford University Press, 2010)
The Low Countries - an area roughly embracing the present-day kingdoms of the Netherlands and Belgium - underwent remarkable developments in the Middle Ages. This text charts the social and economic history of this vibrant region from the early medieval period to the 17th century.